Results of structural assessment of the clinical and hygienic condition of periodontal tissues in patients with anatomical and functional disorders of the mucogingival complex - S. M. Karimov; A. I. Khamidov; K. S. Sharipov; A. A. Ismoilov; F. Z. Imomova (Эндодонтия Today, 2025)
AIM. Conduct the structuration of clinical and hygienic condition of nearteeth tissues beside patients with anatomist-functional disorders of mucous-gingival complex.MATERIALS AND METHODS. The clinical and epidemiological study of dentistry status was organized for achievement of the delivered problems, in which have took part 498 patients with caries and parodontal pathology. From the common amount of examined patient beside 167 (33,5%) of them diagnosed anatomistfunctional disorders of mucous-gingival complex, which were divided into 3 groups. In first clinical group 64 (38,3%) patient were enclosed with average threshold of oral cavity, II type of the correlation division free and attached games, average and get fat biotype of the gums, II type of the correlation division free and attached games, II type of the fastening bridle lips, without clinical symptoms needs thresholds, bridles or lateral bridle of mucous oral cavity in correction. In second group entered 57 (34,1%) patient with small threshold of the oral cavity, which had a correlation division free and attached games on II type, fine and average biotype of the gums, and II type of the fastening bridle lips or mucous shell of oral cavity, as well as their hypertrophy, with positive symptom’s needs enumerated anatomical structures in correction. In third group entered 46 (27,6%) patient with afore-mentioned anatomist-functional disorders, discovered in second group, as well as are discovered recession games III, but coronal comparatively apical to border of vestibule recession.RESULTS. Amongst examined patient with average threshold of the oral cavity factors of the index hygiene on Fedorov–Volodkin beside 25 (34,3%) patients corresponded to good level, beside 29 (39,7%) patients they corresponded to satisfactory level, beside 13 (17,8%) patients level hygiene was estimated as unsatisfactory, but beside 6 (8,2%) patient as bad.CONCLUSIONS. Factors of the hygienic condition of oral cavity beside patient with anatomist-functional disorders of mucous-gingival complex in greater degree were indicative of insufficient satisfactory level, that can be the full-fledged moving conditioned by impossibility of the performing the toothbrush when cleaning teeth.